2014
DOI: 10.3389/fnagi.2014.00066
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori filtrate impairs spatial learning and memory in rats and increases β-amyloid by enhancing expression of presenilin-2

Abstract: Helicobacter pylori (H. pylori) infection is related with a high risk of Alzheimer's disease (AD), but the intrinsic link between H. pylori infection and AD development is still missing. In the present study, we explored the effect of H. pylori infection on cognitive function and β-amyloid production in rats. We found that intraperitoneal injection of H. pylori filtrate induced spatial learning and memory deficit in rats with a simultaneous retarded dendritic spine maturation in hippocampus. Injection of H. py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 51 publications
(67 reference statements)
1
55
0
Order By: Relevance
“…We agree with Kountouras's hypothesis that H. pylori contributes to AD by sharing homologous epitopes with nerve components, thereby triggering autoimmune insults to brain neurons, and finally resulting in AD [5]. A recent study further links H. pylori infection with AD pathologies and suggests that intraperitoneal injection of H. pylori filtrate can promote Ab42 production by enhancing c-secretase and subsequently impairing cognitive performance in a rat model [6]. These studies suggest that autoimmune reactions to brain components might contribute to AD.…”
supporting
confidence: 91%
“…We agree with Kountouras's hypothesis that H. pylori contributes to AD by sharing homologous epitopes with nerve components, thereby triggering autoimmune insults to brain neurons, and finally resulting in AD [5]. A recent study further links H. pylori infection with AD pathologies and suggests that intraperitoneal injection of H. pylori filtrate can promote Ab42 production by enhancing c-secretase and subsequently impairing cognitive performance in a rat model [6]. These studies suggest that autoimmune reactions to brain components might contribute to AD.…”
supporting
confidence: 91%
“…Wang et al. demonstrated that injection of H. pylori but not Escherichia coli filtrates induces spatial learning and memory deficit in rats and increases Aβ 42 both in the hippocampus and in the cortex, by enhancing the activity of γ‐secretase, thereby inducing cognitive impairment via an interruption of the synaptic function. These authors also investigated the effect of H. pylori on tau phosphorylation and showed that H. pylori filtrates induce tau hyperphosphorylation at several AD‐related tau phosphorylation sites in rat brains with glycogen synthase kinase‐3β (GSK‐3β) activation.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…In this regard, Baudron et al [31], by investigating the impact of H. pylori infection on the brain of non-Alzheimer's disease (AD) predisposed mice, showed that H. pylori strain SS1 and Helicobacter felis infection induce gastric inflammation compared to noninfected mice, but without induction of brain neuroinflammation or amyloid-b (Ab) deposition. Wang et al [32] demonstrated that injection of H. pylori but not Escherichia coli filtrates induces spatial learning and memory deficit in rats and increases Ab 42 both in the hippocampus and in the cortex, by enhancing the activity of c-secretase, thereby inducing cognitive impairment via an interruption of the synaptic function. These authors also investigated the effect of H. pylori on tau phosphorylation and showed that H. pylori filtrates induce tau hyperphosphorylation at several AD-related tau phosphorylation sites in rat brains with glycogen synthase kinase-3b (GSK-3b) activation.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Consistent associations with the Greek data were consequently shown in studies from France and in two large-scale epidemiological studies from the USA (one mentioned by the authors [1]) [5], supporting a role for Hp-I in AD pathobiology. In this respect, recent experimental data indicate that intraperitoneal injection of Hp filtrate, but not Escherichia coli, increases Ab42 production by enhancing the activity of c-secretase, thereby inducing cognitive impairment through interrupting the synaptic function [6].…”
mentioning
confidence: 99%